Lower Trait Stability, Stronger Normative Beliefs, Habitual Phone Use, and Unimpeded Phone Access Predict Distracted College Student Messaging in Social, Academic, and Driving Contexts - Briskin, Julia L.; Bogg, Tim; Haddad, Jesse (Frontiers in Psychology, 2018)
The goal of the present study was to test two models of phone messaging behaviors among college students – a sociocognitive connection model and a cybernetic personality system model – across three contexts, where messaging behaviors represented disengagement from the primary context: a meal time with friends, attending class, and driving. Using a sample of university students (N = 634), path analyses with boot-strapping procedures were used to model direct and indirect effects of behavioral, social cognition, and personality trait predictors of primary context disengagement via message checking, message reading, and message sending behaviors. Internal and comparative model fit information showed the cybernetic personality system model represented the data well across all three contexts. Across the contexts, phone related habits and normative beliefs about phone usage mediated relations between personality traits and messaging behaviors. In addition, stronger normative beliefs for messaging behaviors and stronger phone related habits predicted unimpeded physical phone access across the contexts. Across contexts, more frequent messaging behaviors were most strongly predicted by the variance shared by low trait self-discipline, high trait anxiety, and high trait altruism via phone-related habits. The results are discussed in terms of the predictive utility of testing process models of messaging behaviors across varying contexts, as well as possible forms of intervention for reducing primary context disengagement via messaging behaviors.